General Anesthesia Technique in Tetralogy of Fallot Patient Undergo Tooth Extraction Surgery - Iwan Dwi Cahyono; Hari Hendriarto Satoto; Shazita Adiba Martyarini (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2019)
Background: Tetralogy of fallot is one of the congenital cyanotic heart disease that is often found in children. The disorder has four features, a ventricular septal defect (VSD), aortic overriding, infundibulary stenotic, and hypertrophy right ventricular. Like other congenital heart disease, tetralogy of fallot sometimes related to fatal complications, such as bacterial endocarditis which was related to dental infections. Anesthetic management in tetralogy of Fallot is often described in patients with known cardiac disease. Perioperative considerations include preoperative preparation for surgery, intraoperative anesthetic management, and common postoperative issues in the intensive care unit.Case: A three-year-old boy had history of Tetralogy of Fallot. He has many severe early childhood caries. From the physical examination, many severe caries and roots gangrene was found in both jaws. He was planned to get teeth extraction under general anesthesia.Discussion: Tetralogy of fallot (TOF) is a congenital cyanotic heart disease that is often found in children, approximately around of 7–10% from overall congenital heart disease in children. Children with TOF have an increased risk of bacterial endocarditis. Invasive procedure was performed under general anesthesia. Patient was successfully operated under general anesthesia.Conclusion: Tetralogy of Fallot is a congenital cyanogenic heart disease that is a challenge for anesthetist. General anesthesia is the best suitable anesthetic technique in instable patient.